Peran Perempuan Pesisir Terhadap Kesejahteraan Keluarga Di Kelurahan Sapolohe Kecamatan Bontobahari Kabupaten Bulukumba - Andira Nurqalbi; Irwanti Said; Haeruddin (Universitas Islam Negeri Alauddin Makassar, 2024)
The aim of this research is to find out how coastal women's economic activities help improve family welfare and what factors encourage coastal women to carry out economic activities in Sapolohe Village, Bontobahari District, Bulukumba Regency. This type of research is classified as qualitative, using sociology as a scientific approach to analyzing research results. The results of this research show that the forms of economic activity of coastal women in improving family welfare include working as seaweed binders/panyikko bibi', sea catch traders, and culinary trading businesses. The factors that encourage coastal women to carry out economic activities include: Economic factors, including: the husband's relatively low income level, increasing family needs, and the number of family dependents. Educational factors, namely the low level of education possessed by coastal women as well. Social and cultural factors, including: increasing social status, competing to develop oneself, certain interests and abilities, and filling free time.